Quantitative Trait Nucleotides Impacting the Technological Performances of Industrial Saccharomyces cerevisiae Strains - Peltier, Emilien; Friedrich, Anne; Schacherer, Joseph; Marullo, Philippe (Frontiers in Genetics, 2019)
The budding yeast Saccharomyces cerevisiae certainly represents the prime industrial microorganism and it is related to many biotechnological fields including food fermentations, biofuel production, green chemistry and drug production. A noteworthy characteristic of this species is the existence of subgroups well adapted to specific processes with some individuals showing optimal technological traits. In the last twenty years, many studies have established a link between quantitative traits and Single Nucleotide Polymorphisms found in hundreds of genes. These natural variations constitute a pool of QTNs (Quantitative Trait Nucleotides) that modulate yeast traits of economic interest for industry. By selecting a subset of genes functionally validated, a total of 284 QTNs were identified. Their distribution across pan and core genome and their frequency within the 1,011 Saccharomyces cerevisiae genomes were analyzed. Here, we review their phenotypic impact and discuss the opportunities and the limits of their use for industrial strain selection.